2016
DOI: 10.1039/c5ja00501a
|View full text |Cite
|
Sign up to set email alerts
|

On the applicability and performance of the single particle ICP-MS nano-dispersion characterization method in cases complicated by spectral interferences

Abstract: The spectral interference effects occurring in SP-ICP-MS are discussedviathe examples of the measurement of Fe2O3, Cr2O3, and ZnO particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 47 publications
0
23
0
6
Order By: Relevance
“…In case of compact, single component, spherical NPs, the measured intensity is in a cubic relation with the particle diameter. Through the evaluation of the signal histograms, the technique can provide information about the presence, size distribution, number concentration, elemental or isotopic composition of nanoparticles [21][22][23][24]. In our previous studies, we demonstrated that not only single component or homogenous (random) alloy spherical NPs can be analyzed, and additional information, such as the structure and aspect ratio, can also be obtained by the spICP-MS method [25,26].…”
Section: Numerousmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of compact, single component, spherical NPs, the measured intensity is in a cubic relation with the particle diameter. Through the evaluation of the signal histograms, the technique can provide information about the presence, size distribution, number concentration, elemental or isotopic composition of nanoparticles [21][22][23][24]. In our previous studies, we demonstrated that not only single component or homogenous (random) alloy spherical NPs can be analyzed, and additional information, such as the structure and aspect ratio, can also be obtained by the spICP-MS method [25,26].…”
Section: Numerousmentioning
confidence: 99%
“…Kálomista et al [24] and later Bolea-Fernandez et al [28] showed that the collision/reaction cell technology can be used advantageously in spICP-MS measurements as well for diminishing spectral interferences without sacrificing much of the size detection limits or precision of the obtained data.…”
Section: Numerousmentioning
confidence: 99%
“…Az elemi Ti tüdőmintákban lévő teljes koncentrációjának meghatározása a SZTE Szervetlen és Analitikai Kémiai Tanszékén történt, induktív csatolású plazma-tömegspektrometria (ICP-MS, kvantitatív elemanalitikai módszer) alkalmazásával, savas (HNO 3 + HCl) roncsolást követően [24,25]. A biokémiai vizsgálatok elsősorban az alsó légúti alveolaris régió celluláris (alveolaris epithel, macrophag) szintű károsodásainak (akut/krónikus gyulladás, sejtpusztulás) detektálására fókuszáltak.…”
Section: Analitikai éS Kórszövettani Vizsgálatokunclassified
“…Data evaluation in spICP-MS was performed on the histograms (frequencycount diagrams) produced from the time-resolved signal traces, as described in ref. 15. Data processing was performed using Agilent MassHunter (Santa Clara, California, USA) and OriginLab Origin (Northampton, Massachusetts, USA) soware.…”
Section: Instrumentation and Data Evaluationmentioning
confidence: 99%
“…Single particle, or particle-mode, ICP-MS (spICP-MS) is a novel nanoparticle (NP) characterization technique, which is recently gaining increasing attention in the literature owing to its versatility and high throughput. [12][13][14][15] In this technique, sensitive ICP-MS spectrometers are used in the time-resolved mode for the measurement of dilute nanodispersions (particle concentrations less than 10 5 mL À1 are adequate). The nanoparticles get atomized and ionized in the plasma.…”
Section: Introductionmentioning
confidence: 99%